THE EXISTENCE OF THE MARRIAGE DISPENSATION IN MAJENE RELIGIOUS COURT (Study of Maqasid Shari'ah) - Alimuddin, Hardiyanti; Kurniati; Asni; Achmad Musyahid (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This field research provides an overview and factual and explains the various relationships of all the data obtained. This research was conducted in Majene and precisely in the working area of the Majene Religious Court. The study is based on an application for marriage dispensation. Instruments used are researchers, observation, interview, and documentation data. The judge's consideration in granting or rejecting the application for marriage dispensation at the Majene Religious Court is the completeness of the administration at the time of applying for marriage dispensation following Perma No. 5 of 2019, and there is no pro; there on marriage as in Article 8 of Law No. 1 of 1974 concerning Marriage, while still taking into account the aspects of benefit and mudharatan arising from the granting of the application for marriage dispensation.